2006
DOI: 10.1016/j.virol.2006.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Human polyomavirus JCV late leader peptide region contains important regulatory elements

Abstract: Transcription is a complex process that relies on the cooperative interaction between sequence-specific factors and the basal transcription machinery. The strength of a promoter depends on upstream or downstream cis-acting DNA elements, which bind transcription factors. In this study, we investigated whether DNA elements located downstream of the JCV late promoter, encompassing the late leader peptide region, which encodes agnoprotein, play regulatory roles in the JCV lytic cycle. For this purpose, the entire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 66 publications
2
47
0
Order By: Relevance
“…We have also previously reported that alterations in the protein kinase C (PKC) phosphorylation sites of JCV agnoprotein (conversion of Ser7, Ser11, and Thr21 to Ala) resulted in phenotypes that are unable to sustain the viral replication cycle (19). Deletion of either the intrinsically disordered Cterminal region (the sequence from amino acids 51 to 71) (2,79) or internal sequences containing the ␣-helix region (amino acids 17 to 42) (7) resulted in a replication-incompetent virus. Recent fine mapping studies of the multimerization (␣-helix) domain of agnoprotein also revealed the involvement of this domain in determining the stability of agnoprotein as well as in regulation of the splicing of the viral late transcripts (1).…”
Section: Discussionmentioning
confidence: 99%
“…We have also previously reported that alterations in the protein kinase C (PKC) phosphorylation sites of JCV agnoprotein (conversion of Ser7, Ser11, and Thr21 to Ala) resulted in phenotypes that are unable to sustain the viral replication cycle (19). Deletion of either the intrinsically disordered Cterminal region (the sequence from amino acids 51 to 71) (2,79) or internal sequences containing the ␣-helix region (amino acids 17 to 42) (7) resulted in a replication-incompetent virus. Recent fine mapping studies of the multimerization (␣-helix) domain of agnoprotein also revealed the involvement of this domain in determining the stability of agnoprotein as well as in regulation of the splicing of the viral late transcripts (1).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 shows the locations of the additional mutants that were generated, as well as the locations of the predicted host cell protein binding sites (Akan et al, 2006). Mad-1 PtΔ300-349 encompasses the region from the beginning of the JCV CPN deletion to the start of binding site III.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, Mad-1 PtΔ411-442 is the region between binding sites III and II. As controls, we used the previously characterized viruses Mad-1 Pt, a start codon deletion mutant, Mad-1 Del, a full agnogene deletion mutant (Akan et al, 2006), and Mad-1 C-Agno, JCV Mad-1 with the JCV CPN agnogene, which has a deletion of nucleotides 300-442 (Ellis et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations